Research note: High levels of lead and arsenic in imported dried black soldier fly larvae: implications for backyard poultry supplementation - Mikayla F.A. Baxter; Alissa H. Moritz (Poultry Science)
Insects provide essential nutrition to poultry, however, the feedstock fed to the insects and the age and method of processing, can significantly impact nutrient and safety levels. The purpose of this research was to examine the nutrient and safety of black solider fly larvae (BSFL). Over a two-year period, 21 BSFL were purchased from retail and online establishments and blindly labeled and sent to accredited laboratories for proximate analysis, heavy metal analysis and antibiotic residues. No samples contained detectable levels of antibiotic residues. On average, Chinese-sourced dried black solider fly larvae (DBSFL), had 25X more lead and 8X more arsenic than North American, both values were statistically different. Chinese-sourced DBSFL had significantly lower phosphorus, protein, magnesium, potassium and manganese as compared to those from North America (p<0.05). While North American DBSFL had significantly lower fat and iron levels than Chinese-sourced DBSFL. Many of the imported products did not have or were not compliant with current US regulatory labeling requirements. The mislabeling and higher levels of heavy metals in DBSFL is concerning as it not only can affect the health of back yard flocks and humans via consumption of eggs from backyard flocks but also has the potential to contaminate the environment. Keywords: Dried black solider fly larva; Heavy Metal; Layer; Backyard chicken